encryption - Prove the decryption by counter mode is correct -


as review question have prove decryption process of counter mode correct. how prove it? no other information given.

encryption: cj = e(k, counter + j -1) ⊕ pj  decryption: pj = e(k, counter + j -1) ⊕ cj 

pj = e(k, counter + j -1) ⊕ cj 

replace cj = e(k, counter + j -1) ⊕ pj

cj = e(k, counter + j -1) ⊕ e(k, counter + j -1) ⊕ pj  

since x⊕x=0 (the encrypted counter xored itself) , 0⊕x=x

pj = 0 ⊕ pj  pj = pj 

qed


Comments

Popular posts from this blog

c++ - llvm function pass ReplaceInstWithInst malloc -

java.lang.NoClassDefFoundError When Creating New Android Project -

Decoding a Python 2 `tempfile` with python-future -